2020
DOI: 10.1111/camh.12374
|View full text |Cite
|
Sign up to set email alerts
|

Self‐harm and self‐regulation in urban ethnic minority youth: a pilot application of dialectical behavior therapy for adolescents

Abstract: BackgroundDifficulties in coping with stress and regulating emotions are transdiagnostic risk factors for self‐harming behavior. Due to sociocultural stressors, ethnic minority adolescents may be at greater risk for self‐regulation difficulties and self‐harm. Dialectical behavior therapy for adolescents (DBT‐A) frames adaptive skill acquisition as a mechanism of change, but few studies have investigated its impact on ethnic minority adolescents’ self‐regulation (i.e. coping, emotion regulation). Therefore, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…This indicates a need for future studies that overrecruit and/or focus exclusively on ethnoracial, sexual, and gender minority groups. To date, these types of studies have been conducted using non-RCT designs, such as pre–post studies of DBT with American Indian/Alaska Native adolescents (Beckstead et al, 2015), ethnic minority youth (Berk et al, 2020; Yeo et al, 2020), and sexual minority veterans (Cohen et al, 2021). Future research utilizing RCT designs and/or larger samples of ethnoracial, sexual, and gender minority participants is needed to expand DBT’s evidence base for individuals from these groups.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a need for future studies that overrecruit and/or focus exclusively on ethnoracial, sexual, and gender minority groups. To date, these types of studies have been conducted using non-RCT designs, such as pre–post studies of DBT with American Indian/Alaska Native adolescents (Beckstead et al, 2015), ethnic minority youth (Berk et al, 2020; Yeo et al, 2020), and sexual minority veterans (Cohen et al, 2021). Future research utilizing RCT designs and/or larger samples of ethnoracial, sexual, and gender minority participants is needed to expand DBT’s evidence base for individuals from these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary research provides tentative support for these mechanisms of change. In a non-randomized pilot of DBT-A among a small sample of ethnic minority adolescents, adaptive coping at pretreatment predicted subsequent increased use of DBT skills at post-treatment (Yeo et al, 2020 ). Secondary analysis of McCauley et al ( 2018 ) revealed that adolescents who reported higher emotion dysregulation at baseline, and whose parents reported greater psychopathology and emotion dysregulation demonstrated greater reduction in self-harm following 6-months of DBT-A treatment (Adrian et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of any of these components would indicate emotional dysregulation (Gratz and Roemer, 2004). The above definition has been shown to be clinically useful, with research demonstrating a relationship between the emotional regulation components and harmful behaviours (Gratz, 2007;Peh et al, 2017;Velotti et al, 2020;Yeo et al, 2020).…”
Section: Self-harm Emotional Regulationmentioning
confidence: 99%